If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12x + -10 = -11x + 16 Reorder the terms: -10 + -12x = -11x + 16 Reorder the terms: -10 + -12x = 16 + -11x Solving -10 + -12x = 16 + -11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11x' to each side of the equation. -10 + -12x + 11x = 16 + -11x + 11x Combine like terms: -12x + 11x = -1x -10 + -1x = 16 + -11x + 11x Combine like terms: -11x + 11x = 0 -10 + -1x = 16 + 0 -10 + -1x = 16 Add '10' to each side of the equation. -10 + 10 + -1x = 16 + 10 Combine like terms: -10 + 10 = 0 0 + -1x = 16 + 10 -1x = 16 + 10 Combine like terms: 16 + 10 = 26 -1x = 26 Divide each side by '-1'. x = -26 Simplifying x = -26
| Sin^4(3x/2) | | 6x^2y+8xy+2=0 | | 7(2b+1)-3b=29 | | 4a(a^4)7a=a(4a^3)+20 | | 6x^2y+8xy+2= | | 4x/4=29/8 | | 20/10=N/2 | | Sinx=0.234 | | -2x-6+-0.25x-3+90=180 | | 2138.9994=3.14r^2 | | -32c/(5*9) | | X11/4 | | T/5=-5/7 | | 2318.9994=3.14r^2 | | 3x-17*5=-66 | | 4x+5y=10.45 | | 2.27*34= | | 0.16(y-6)+0.10y=0.04y-0.3 | | 4(5+3x)=-52 | | 7(a+2)=-2(a-2) | | 3x+1y=3.85 | | 12n=162 | | (5a-3b)+(2a+6b)= | | x(x-6)=x^2+5x+4 | | Y+23=111 | | 2(t-4)+6t=4(2t+3)-9 | | 4x-3+73=90 | | 4s-10=8-2s | | X-24=53 | | 4ln(5x+4)=22 | | g(3y)x-2x^2= | | 3(2c+1)=2(4c-1) |